Morphological changes in the backwater of the Jeziorsko Reservoir against the background of changes in the bottom of the Warta River valley between the Widawka estuary and Uniejów town in the Anthropocene - Rdzany, Zbigniew; Szmidt, Aleksander; Kossowski, Maciej (Acta Geographica Lodziensia, 2024)
The article analyses the youngest morphological changes in the central section of the Warta valley floor between Woźniki village and Uniejów town. Although various manifestations of human impact have been recorded in landforms and sediments since at least the Bronze Age, these processes became more intense in the first half of the 19th century. At that time, the construction and expansion of flood embankments, carried out in stages, was of great importance, as was the construction of the Jeziorsko Dam Reservoir with accompanying hydrotechnical structures and devices. The flood embankments in sections outside the reservoir resulted in a radical separation of morphogenetic processes in the area between the embankments and in the outer two belts of the embankment. In the vicinity of the Jeziorsko Reservoir, characteristic morphodynamic zones with variable process dynamics have developed, functioning depending on water level fluctuations and flow variability in the Warta riverbed: the coastal zone and the delta zone of the reservoir. The research, focused on a detailed analysis of changes in the relief of the delta, allowed to prove that a single flood can change the degree of siltation of the reservoir, just like several dozen years of constant accumulation. It was also found that the effects of floods can be better assessed only after a few years rather than after a few months after the event